2017
DOI: 10.1111/acel.12682
|View full text |Cite
|
Sign up to set email alerts
|

Loss of SIRT2 leads to axonal degeneration and locomotor disability associated with redox and energy imbalance

Abstract: SummarySirtuin 2 (SIRT2) is a member of a family of NAD +‐dependent histone deacetylases (HDAC) that play diverse roles in cellular metabolism and especially for aging process. SIRT2 is located in the nucleus, cytoplasm, and mitochondria, is highly expressed in the central nervous system (CNS), and has been reported to regulate a variety of processes including oxidative stress, genome integrity, and myelination. However, little is known about the role of SIRT2 in the nervous system specifically during aging. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 48 publications
2
30
0
Order By: Relevance
“…A very interesting recent study demonstrated that release of cytokines such as IL-1β and TNFα by classically activated neuroinflammatory microglia induce a subtype of astrocytes termed A1-reactive astrocytes that are neurotoxic for axotomized neurons; these astrocytes are present in patients with human neurodegenerative diseases 46 . Finally, in a totally different way but in agreement to the detrimental effects of the SIRT2 loss-of-function is a recent study reporting axonal degeneration observed in the aged SIRT2-KO mice 47 .…”
Section: Discussionmentioning
confidence: 89%
“…A very interesting recent study demonstrated that release of cytokines such as IL-1β and TNFα by classically activated neuroinflammatory microglia induce a subtype of astrocytes termed A1-reactive astrocytes that are neurotoxic for axotomized neurons; these astrocytes are present in patients with human neurodegenerative diseases 46 . Finally, in a totally different way but in agreement to the detrimental effects of the SIRT2 loss-of-function is a recent study reporting axonal degeneration observed in the aged SIRT2-KO mice 47 .…”
Section: Discussionmentioning
confidence: 89%
“…The enzymatic activity of SIRT2 is dependent on nicotinamide adenine dinucleotide (NAD + ), and it not only catalyzes the deacetylation of histone substrates, but also that of non-histone substrates (Landry et al, 2000). SIRT2 thus regulates a large spectrum of physiological processes such as genome stability, mitosis, nutrient metabolism, aging, mitochondrial function, autophagy, myelination, apoptosis, antioxidant mechanisms and cell motility (North and Verdin, 2007;Maxwell et al, 2011;Liu et al, 2014Liu et al, , 2017Braidy et al, 2015;Gomes et al, 2015;Fourcade et al, 2017). Recent studies have indicated that SIRT2 is implicated in several aging-related neurodegenerative diseases, and the fact that its expression increases not only with age but also in PD models suggests its key role in this particular disease (Harting and Knöll, 2010;Maxwell et al, 2011;Poulose and Raju, 2015;Sun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative Medicine and Cellular Longevity through an increase in SIRT1 expression with age, suggesting that Sirt1 is involved in longevity [93,94]. SIRT 2 is closely related to age-related diseases, such as Alzheimer's disease (AD) and Parkinson's [95]. Studies have shown that inhibition of SIRT2 expression could delay the progression of these diseases.…”
Section: Vascular Smooth Muscle Cellsmentioning
confidence: 99%